Finding New Views on Unmentionable Diseases: On the Fiction of Lu Min. (2nd July 2020) - Zhang, Li; Patton, Simon
Abstract : Lu Min's fiction is alive with pathologies—her characters display outward signs of scopophilia, skin conditions, spells of inexplicable dizziness, or vomiting, as well as social pathologies like compulsive lying or incestual tendencies. But what drives these "unmentionable diseases" in Lu Min's fiction? What are their causes, symptoms, or remedies? According to Zhang Li, the underlying conditions that provoke and result from these maladies arise from a compulsive need for her characters to overstep their proscribed boundaries and norms. Lu Min's characters yearn to become what they are not, and in the face of their helplessness, they must grapple with not becoming "somebody else." From Issue 2 of Chinese Arts and Literature, published by Xanadu Press, 2016; reprinted by permission of Chinese Arts and Literature .